Fungsi Dan Makna Ruang Pada Rumah Adat Mbaru Niang Wae Rebo - Monica Louis (Intra, 2015)
Mbaru Niang is a traditional house at Wae Rebo in form of a cone, with total amount of seven houses with their own exoticsm. The architectural of Mbaru Niang always be the main focus of general discussion, while the interior and other functuions on every level of the shape of the rooms is rarely researched. As for Wae Rebo society, Mbaru Niang is a part of themselves, every level of the rooms has its own different purposes and meaning. This research aims to enrich the data analysis, and to give more knowledge to the successor generations. Semiotic methode of Pierce is used on this research to identify every signs of the essence through the variety of the icons, indexes, and symbols. The result of this Piercian method applied on the objects mentioned could lead to a conclusion on the purpose and essence of rooms of a Mbaru Niang, especially on Mbaru Gendang.